The Contrasting Role of Extracellular Vesicles in Vascular Inflammation and Tissue Repair - Oggero, Silvia; Austin-Williams, Shani; Norling, Lucy Victoria (Frontiers in Pharmacology, 2019)
Extracellular vesicles are a heterogeneous family of vesicles, generated from different subcellular compartments and released into the extracellular space. Composed of a lipid bilayer encompassing both soluble cytosolic material and nuclear components, these organelles have been described recently as novel regulators of intercellular communication between adjacent and remote cells. Due to their diversified composition and biological content, they portray specific signatures of cellular activation and pathological processes; their potential as diagnostic and prognostic biomarkers have raised significant interest in cardiovascular diseases. Circulating vesicles, especially those released from platelets, leukocytes and endothelial cells have been found to play a critical role in activating several fundamental cells within the vasculature, including endothelial cells and vascular smooth muscle cells. Their intrinsic activity and immunomodulatory properties lends them to not only promote vascular inflammation, but also enhance tissue regeneration, vascular repair and indeed resolution. In this review we aim to recapitulate the recent findings concerning the roles played by EVs that originate from different circulating cells, with particular reference to their action on the endothelium. We focus herein, on the interaction of platelet and leukocyte EVs with the endothelium. In addition, their potential biological function in promoting tissue resolution and vascular repair will also be discussed.